Epidemiology of Lymphedema-related admissions in the United States: 2012–2017. (December 2020) - Lopez, Marcos; Roberson, Mya L.; Strassle, Paula D.; Ogunleye, Adeyemi
Abstract: Background: Lymphedema is a debilitating chronic condition with no definitive curative treatment. There is a paucity of data on prevalence, mortality and burden of care in the United States. This study aimed to describe hospitalizations due to lymphedema and identify factors associated with poor outcomes. Study design: We performed a retrospective analysis of the Healthcare Cost and Utilization Project National Inpatient Sample for lymphedema-related hospitalizations from 2012 to 2017. All adults admitted with a primary diagnosis of lymphedema or a primary diagnosis of extremity cellulitis and secondary diagnosis of lymphedema were included. Weights were used to obtain national estimates and complex sampling structure was accounted for using survey methods. Chi-squared tests were performed to assess the association between patient demographics, hospital characteristics, and inpatient mortality. Results: Between 2012 and 2017, there were an estimated 165, 055 lymphedema admissions in the United States. The vast majority of hospitalizations were for cellulitis (92%), lower extremity disease (88%), and were admitted through the emergency room (77%). Median length of stay was 3.61 days (IQR 2.24–5.77) and inpatient mortality was 0.03% ( n = 505). Age >80yrs (OR 3.83, 95% CI 1.72, 8.52) and Charlson comorbidity index ≥3 (OR 4.13, 95% CI 2.19, 7.79) were associated with increased risk of inpatient mortality. Conclusion: Although mortality is low, lymphedema-related hospitalizations are a significant burden to the US healthcare system. Counseling older lymphedema patients with comorbidities on early symptoms and signs of infection and prompt treatment of same may reduce mortality. Highlights: Mortality from lymphedema-related hospitalization is low. Hospitalizations are a significant burden to the US healthcare system. Older lymphedema patients with comorbidities are at higher risk for mortality. Counseling on features of infection and prompt treatment may reduce mortality.